Gymnema Sylvestre (Retz.) R.Br. Ex Sm.: A Botanical, Ethnopharmacological, Phytochemical, And Pharmacological Overview (Journal of Pharmaceutical Negative Results, 2023)
Gymnema sylvestre (Retz.) R.Br. ex Sm. is a perennial climbing shrub found over the tops of woody trees in tropical forest of India. It is a miracle plant having great anti-diabetic potential. The phytoconstituents of Gymnema sylvestre were isolated and their chemistry and structures were studied and elucidated. An inspection of literature revealed some extraordinary pharmacological activities of this plant. The present review is an effort to emphasize the various traditional use as well as, phytochemistry, pharmacological uses therapeutic properties on G. sylvestre.